If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 7)(x + -1) = (x + 2)(x + 2) Reorder the terms: (7 + x)(x + -1) = (x + 2)(x + 2) Reorder the terms: (7 + x)(-1 + x) = (x + 2)(x + 2) Multiply (7 + x) * (-1 + x) (7(-1 + x) + x(-1 + x)) = (x + 2)(x + 2) ((-1 * 7 + x * 7) + x(-1 + x)) = (x + 2)(x + 2) ((-7 + 7x) + x(-1 + x)) = (x + 2)(x + 2) (-7 + 7x + (-1 * x + x * x)) = (x + 2)(x + 2) (-7 + 7x + (-1x + x2)) = (x + 2)(x + 2) Combine like terms: 7x + -1x = 6x (-7 + 6x + x2) = (x + 2)(x + 2) Reorder the terms: -7 + 6x + x2 = (2 + x)(x + 2) Reorder the terms: -7 + 6x + x2 = (2 + x)(2 + x) Multiply (2 + x) * (2 + x) -7 + 6x + x2 = (2(2 + x) + x(2 + x)) -7 + 6x + x2 = ((2 * 2 + x * 2) + x(2 + x)) -7 + 6x + x2 = ((4 + 2x) + x(2 + x)) -7 + 6x + x2 = (4 + 2x + (2 * x + x * x)) -7 + 6x + x2 = (4 + 2x + (2x + x2)) Combine like terms: 2x + 2x = 4x -7 + 6x + x2 = (4 + 4x + x2) Add '-1x2' to each side of the equation. -7 + 6x + x2 + -1x2 = 4 + 4x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 -7 + 6x + 0 = 4 + 4x + x2 + -1x2 -7 + 6x = 4 + 4x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 -7 + 6x = 4 + 4x + 0 -7 + 6x = 4 + 4x Solving -7 + 6x = 4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -7 + 6x + -4x = 4 + 4x + -4x Combine like terms: 6x + -4x = 2x -7 + 2x = 4 + 4x + -4x Combine like terms: 4x + -4x = 0 -7 + 2x = 4 + 0 -7 + 2x = 4 Add '7' to each side of the equation. -7 + 7 + 2x = 4 + 7 Combine like terms: -7 + 7 = 0 0 + 2x = 4 + 7 2x = 4 + 7 Combine like terms: 4 + 7 = 11 2x = 11 Divide each side by '2'. x = 5.5 Simplifying x = 5.5
| -x-x+5x-3=3x+5 | | -(5/9)x=2 | | -10a+3(8+8r)=24+r | | .2x+3.5=16.1 | | 2(2x-1)=26 | | 0.25y-0.01x=0.005 | | y=12-9 | | 6(3.14)=w-6(3.14) | | ((x-1)/3)-2=((x-5)/4) | | 2x+18y=18 | | 3x-11=2x+33 | | 14-b=8 | | -4+3x=7x+x+14x-8x | | 65=-6-x | | 81=x+181 | | 6/10-2/100 | | V-10=-19 | | -4+3x=7x+x+14-8x | | 9a-6=8a+1 | | 2x+2x+x+3x+3=24 | | 2x+0=5y-0 | | 5x+6=9x+3+8x | | 7bf^4-7bk^4= | | 6u(-5u^4)=0 | | 2a-1=3(a+1)+7a+5 | | X+4+5x+3+4x=21 | | (y^-1/4)^1/6 | | 9-3v=0 | | 17x-36=12x+7 | | x+8=-72 | | 2(x-6)=3(x-4) | | y^(3/2)-10y |